Venous Thromboembolism among Cancer Patients: A Review - Galila F. Zaher (Journal of King Abdulaziz University: Medical Sciences, 2023)
Venous thromboembolism is associated with adverse outcomes in patients with cancer. It has a multifactorial pathogenesis and a different expression pattern among various types of malignancies. Administration of anticoagulants forms the key therapeutic approach towards the management of venous thromboembolism. However, this is associated with increased risk of bleeding during the treatment. Chemotherapy, surgery, use of central venous catheters and radiotherapy represent major risk groups, which lead to increased venous thromboembolism and bleeding. Consequently, risk stratification can be an important tool, which can provide better thromboprophylaxis in a patient-based manner. The present review summarizes the epidemiology, pathogenesis and risk factors of venous thromboembolism in cancer patients. In addition, indications for different strategies towards challenging thromboprophylaxis and management of venous thromboembolism in cancer patients are also deliberated.